Exploring The Role of Nature of Sports in Lifestyle and Sports Engagement of Student-Athletes - Garban, Cleven; Reillo, Lhidie Joy; Longakit, Jet Clayton (Sports Medicine Curiosity Journal, 2023)
This study aims to explore the moderating effect of the nature of sport on the relationship between lifestyle and sports engagement for different types of sports and how it affects each student-athlete. A sample comprised of 408 consisting of 29.9% individual sports (n=122), 18.87% dual sports (n=77), and 51.23% (n=209) student-athletes answered a packet of questionnaires assessing lifestyle and sport engagement. The results showed that overall lifestyle is a significant predictor of sports engagement, as students who demonstrate good exercise habits, engage in regular exercise, and maintain good nutrition are more likely to engage in sports. Interestingly, the type of sport did not significantly affect sports engagement. These findings provide empirical evidence that the type of sport does not moderate the relationship between lifestyle and sports engagement, which suggests that student-athletes can participate in any sport of their choice, whether it is an individual or dual sport or a team sport, to support them in achieving their maximum potential. However, there may be other factors that moderate the relationship between student-athletes' lifestyles and sports engagement that require further investigation.